Arsenic immobilization in soil affected by mining waste using waste‐derived functional hydrochar and iron‐encapsulated materials. Issue 1 (5th January 2023) - Haris, Muhammad; Netherway, Pacian; Eshtiaghi, Nicky; Paz‐Ferreiro, Jorge
Abstract: Arsenic (As) contamination is a widespread problem. Continued and concerted effort in exploring sustainable remediation strategies is required, with in situ immobilization emerging as a promising option. This work valorized a waste by‐product from olive ( Olea europaea L.) milling into functional hydrochar (HC). The HC was then transformed into iron oxide–encapsulated carbon with three different iron loading rates (10, 25, and 50% w/w of iron chloride hexahydrate added to the olive mill waste feedstock). The HC and the three iron oxide–encapsulated carbon materials were then tested in a pot trial using a 3% w/w application rate as a means to immobilize As in a mining‐contaminated soil (2, 580 ± 110 mg kg −1 As). After a 45‐d incubation period, the effect of adding the amendments on As mobility and bioaccessibility compared with an untreated control was measured using a sequential extraction procedure and in vitro bioaccessibility, respectively. All four treatments resulted in a decrease in mobility and in vitro bioaccessibility as compared with the control. Specifically, As in the mobile phases was up to 35% less than the in control, whereas bioaccessibility was 21.8% in the control and ranged from 17.5 to 12.3% in the treatments. The efficiency of amendments to immobilize As increased with the iron content of the developed materials. This work positions HCs and iron oxide–encapsulated carbon materials produced from olive mill waste as promising options to immobilize As in situ. Core Ideas: Hydrochar and iron oxide–encapsulated carbon were used to immobilize arsenic in soil for the first time. Sequential extraction and bioaccessibility procedures were used to investigate As mobility. All amendments were effective in immobilizing arsenic. Higher iron loadings resulted in less As in mobile fractions and less bioaccessibility.